Creation of a Medical Student Training to Improve Comfort Providing Trauma-Informed Care to Sexual Assault Survivors - Daniel J. Gore; Melissa Prusky; Chloe J. E. Solomon; Kaitlynn Tracy; Joshua Longcoy; Jaclyn Rodriguez; Paul Kent (Association of American Medical Colleges, 2021)
Introduction Sexual violence is a significant public health concern in the United States, affecting as many as one in two women and one in four men. However, few medical schools offer education on trauma-informed communication with patients who disclose sexual assault (SA). The goal of this training was to provide medical students with an understanding of how to empathically respond to SA disclosures, collect pertinent medical information while avoiding retraumatization, and empower patients to feel in control of their care. Methods One hundred forty-nine second-year medical students at Rush Medical College attended a 1-hour didactic lecture discussing the needs of SA survivors followed by small-group sessions during which they practiced trauma-informed communication skills. Students completed anonymous pre- and postsession surveys featuring nine Likert-scale questions that assessed comfort level providing trauma-informed care. Results Of the 149 attendees, 88 (59%) completed matched pre- and posttraining surveys that demonstrated significant improvement in all assessed metrics of trauma-informed care, including comfort collecting information, empowering survivors, and responding to and normalizing patients' concerns. Two weeks after completing the training, all 149 students also correctly answered a free-response question testing retention of key training takeaways on their Sexuality and Reproduction final exam. Discussion The training significantly improved medical student comfort in providing trauma-informed care across all collected metrics. The training can be feasibly reproduced at other institutions so that future physicians across specialties can provide trauma-informed care, ideally improving the acute and chronic health outcomes that disproportionately affect SA survivors.